Revolusi Regulasi dalam Ekonomi Syariah: Integrasi Teknologi Digital untuk Optimalisasi Penerapan Prinsip Syariah - Eva Maya Sari; Baidhowi Baidhowi (Jurnal Nuansa : Publikasi Ilmu Manajemen dan Ekonomi Syariah, 2025)
This study examines the phenomenon of the regulatory revolution in the sharia economy through the integration of digital technology to optimize the application of sharia principles. The background of this research departs from the rapid digital transformation, which requires adaptation and reform within the framework of sharia economic regulations to remain relevant and responsive to the challenges of the times. Using a qualitative approach that combines normative-doctrinal analysis and empirical case studies, this study aims to explore how current regulatory developments, the role of digital technology, as well as legal innovation challenges and opportunities arise in the implementation of sharia principles. The results of the study show that the integration of digital technology not only increases efficiency and transparency in the application of sharia principles, but also raises new problems related to the adaptation of conventional legal frameworks. Therefore, cross-sector collaboration and adaptive regulatory reform are needed to optimize the potential of the sharia economy in the digital era.